Attenuated PDGF signaling drives alveolar and microvascular defects in neonatal chronic lung disease - Prajakta Oak; Tina Pritzke; Isabella Thiel; Markus Koschlig; Daphne S Mous; Anita Windhorst; Noopur Jain; Oliver Eickelberg; Kai Foerster; Andreas Schulze; Wolfgang Goepel; Tobias Reicherzer; et al. (EMBO Molecular Medicine)
Abstract Neonatal chronic lung disease (nCLD) affects a significant number of neonates receiving mechanical ventilation with oxygen‐rich gas (MV‐O2). Regardless, the primary molecular driver of the disease remains elusive. We discover significant enrichment for SNPs in the PDGF‐Rα gene in preterms with nCLD and directly test the effect of PDGF‐Rα haploinsufficiency on the development of nCLD using a preclinical mouse model of MV‐O2. In the context of MV‐O2, attenuated PDGF signaling independently contributes to defective septation and endothelial cell apoptosis stemming from a PDGF‐Rα‐dependent reduction in lung VEGF‐A. TGF‐β contributes to the PDGF‐Rα‐dependent decrease in myofibroblast function. Remarkably, endotracheal treatment with exogenous PDGF‐A rescues both the lung defects in haploinsufficient mice undergoing MV‐O2. Overall, our results establish attenuated PDGF signaling as an important driver of nCLD pathology with provision of PDGF‐A as a protective strategy for newborns undergoing MV‐O2.